Screening of filamentous fungi for antimicrobial silver nanoparticles synthesis - Ottoni, Cristiane Angélica [UNESP]; Simões, Marta Filipa; Fernandes, Sara; dos Santos, Jonas Gomes; da Silva, Elda Sabino; de Souza, Rodrigo Fernando Brambilla; Maiorano, Alfredo Eduardo (Springer Nature, 2017)
The present work had the goal of screening a batch of 20 fungal strains, isolated from sugar cane plantation soil, in order to identify those capable of biosynthesis of silver nanoparticles. These nanoparticles are known to have a large and effective application in clinical microbiology. Four strains were found to be capable of biosynthesis of silver nanoparticles. The biosynthesised nanoparticles were characterised by UV–vis spectroscopy, scanning electron microscopy, EDX, and XRD. They were found to have an average size of 30–100 nm, a regular round shape, and potential antimicrobial activity against Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa. The antimicrobial activity was found to be directly related to the nanoparticles concentration. Mycogenic synthesis of nanoparticles is a green biogenic process preferable to other alternatives. Because fungi are great producers of extracellular enzymes this process makes scaling-up an easier task with high importance for clinical microbiology on the fight against microbial resistance, as well as for other industrial applications.
Keywords: Antimicrobial; Filamentous fungi; Mycogenic synthesis; Nitrate-reductase; Silver nanoparticles